Amelia Jane again - Blyton, Enid (Egmont UK Limited, 2014)
A classic childrens story from the worlds best-loved childrens author, Enid Blyton. Amelia Jane is big, bad and the terror of the toy cupboard! In this book, she gives the toys some terrible scares with her mischief and gets poor Teddy to carry her home without him knowing it. But sometimes the toys get their own back...